HUBUNGAN AKSES SOSIAL MEDIA DENGAN PERILAKU PEMILIH DALAM PILKADA SERENTAK 2018 PADA MAHASISWA UNTAG SURABAYA - Norhabiba, Fitri (representamen, 2018)
Social media access is increasingly mushrooming among the students into a uniquething to be studied. Of these habits of students are still considered less concerned with theenvironment, especially for the election of regional heads. Students who are a reflection ofthe current generation are expected to remain one of the indicators of change agents.The type of research is descriptive quantitative. This study will examine aspects ofthe aspects in the uses and gratification associated with voter behavior. The results showedthat there was a negative relationship between the intensity of social media access and voterbehavior. The media still has a role to play as a source of political information for voters butdoes not really affect the attitude of students in their choice.Keywords: voter behavior, social media, current generation, uses gratifications